The Influence of Serious Attitude In Work towards Business Success (Metro Muslim Entrepreneurs) - Murcitaningrum, Suraya; Machsun, Muhammad; Aliyu Gololo, Ibrahim (Universitas Islam Negeri Raden Intan Lampung, 2018)
This paper discusses thei nfluence of seriousattitude in work towards business success of Muslim entrepreneurs as it is known that the seriousness in work can create business success. The purpose of this study is to identify and assess the effect of seriousness attitude in work toward the success of the Muslim entrepreneurs in Metro Regency of Lampung. This study is based on a literature study and understandings of the accumulation of various primary studies conducted on Muslim entrepreneurs around the Islamic Boarding School of Al Muhsin 28 Metro collected through questionnaires. The literature study was conducted to understand the concept of the seriousness in work. The results of the analysis showed that the significant value was 0.020. Since the value of α = 0.01, then the H0 was rejected if α was < 0.01. Based on the analysis, it can be concluded that there is a relation of seriousness in work of Muslim businessmen to business success in Metro Regency. Keywords : Serious Attitude ,Work towards Business Success, Muslim Entrepreneurs